2022
DOI: 10.3847/1538-4365/ac5458
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-seven Eclipsing Quadruple Star Candidates Discovered in TESS Full-frame Images

Abstract: We present a catalog of 97 uniformly vetted candidates for quadruple star systems. The candidates were identified in TESS full-frame image data from sectors 1–42 through a combination of machine-learning techniques and visual examination, with major contributions from a dedicated group of citizen scientists. All targets exhibit two sets of eclipses with two different periods, both of which pass photocenter tests confirming that the eclipses are on target. This catalog outlines the statistical properties of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
1
23
1
Order By: Relevance
“…Note added in proof: Just after the submission of the present manuscript there was published an independent paper dealing with the same topic, Kostov et al (2022). The authors presented a group of 97 doubly eclipsing systems found in the TESS database, but identified with different method (scanning all stars instead of only known eclipsing binaries like we did).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Note added in proof: Just after the submission of the present manuscript there was published an independent paper dealing with the same topic, Kostov et al (2022). The authors presented a group of 97 doubly eclipsing systems found in the TESS database, but identified with different method (scanning all stars instead of only known eclipsing binaries like we did).…”
Section: Discussionmentioning
confidence: 97%
“…Article number, page 4 of 16Zasche & Henzl & Mašek: Catalogue of TESS multiple eclipsers Notes: ♯ -Out-of-eclipse magnitude, V mag from UCAC4 catalogue(Zacharias et al 2013), or Guide Star Catalog II(Lasker et al 2008), * -Independently discovered during preparation of the current manuscript, and recently published inKostov et al (2022). The columns D P , and D S denote the approximate depths of primary and secondary eclipses of both pairs based on the TESS data.Article number, page 5 of 16A&A proofs: manuscript no.…”
mentioning
confidence: 99%
“…Such visual searches are a complement to more automated ones using machine learning algorithms (see e.g. Powell et al 2021 ;Kostov et al 2021 ;Kostov et al 2022 ). The light curves are displayed with Allan Schmitt's LcTools and LcViewer software (Schmitt, Hartman & Kipping 2019 ), which allows for an inspection of a typical light curve in just ∼5 s. It is important to note that 9 million of the studied light curves were of anonymous stars, while 1 million light curves were of preselected eclipsing binaries that were found in the TESS data via machine learning searches (see Powell et al 2021 ;Kruse et al, in preparation).…”
Section: I S C Ov E Ry O F T R I P Ly E C L I P S I N G T R I P L E S...mentioning
confidence: 99%
“…When one of these triples is found, no further vetting of the object is typically needed before concluding that this is a bound triple system (or possibly a higher stellar multiple). By contrast, when a pair of EBs is found in the same photometric aperture, it is not immediately clear whether the two EBs are physically bound or are simply close together on the sky by chance (see the quadruples catalogue of Kostov et al 2022 ), and further vetting in the form of, e.g. radial velocity (RVs) measurements or eclipse timing variations (ETVs) is required.…”
Section: Introductionmentioning
confidence: 99%
“…The age dependence of the short-period binaries (Hwang et al 2020b) can explain the enhancement for a factor of 2, and the rest enhancement of a factor of ∼ 3 can be explained by the result here that the close binary fraction is 2.2 times higher among wide pairs than the field close binary fraction. 2+2 systems are found in other parameter space (Cagaš & Pejcha 2012;Borkovits et al 2018;Powell et al 2021;Kostov et al 2022) and statistical analysis also reports the excess of 2+2 systems (Tokovinin 2014). Therefore, even if the dynamical unfolding may work for initially compact three-body systems to form hierarchical triples, it is seemingly challenging to have initially compact four-body systems unfold to the 2+2 architecture dynamically.…”
Section: Dynamical Unfolding Of Compact Triplesmentioning
confidence: 99%